(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the article, it was determined that the working quality of the combined aggregate roller depends on the mass of the roller, the uniformity of the pressure spring and the physical and mechanical properties of the soil.